Platelet angiotensin II binding in non-pregnant women and in normotensive pregnant and hypertensive pregnant women - Baker, Philip (1991)
A method for measuring human platelet Angiotensin II (All) binding was validated, and characterisation studies involving 67 non-pregnant subjects were performed. Platelets were found to possess high affinity binding sites with many of the characteristics of receptors. No correlation was found between platelet All binding and the rise in intracellular free calcium after ex vivo All infusion, thus formal validation of the binding sites as receptors was not achieved.